Effects of restricted feeding schedule during development and gestation on gilt and sow performance - Schneider, Jason Dean (Kansas State University, 2007)
The overall objective of these experiments was to develop management and feeding programs to increase sow longevity and productivity by improving welfare conditions. In Exp. 1, 208 gestating sows and 288 gestating gilts were utilized to determine the effect of feeding frequency (2 vs. 6) on performance and welfare issues. Feeding frequency had no affect on growth and reproductive performance in gestating sows; however, increasing the feeding frequency did improve the welfare measurements in this trial. Gilts fed six times a day did have increase ADG during d 0 to 42; however, there was no affect on performance from d 42 to farrowing. In Exp. 2 (630 pigs in 4 studies), increasing the feeding frequency (2 vs. 6) of a restricted feeding level increased growth performance of finishing pigs. This affect is likely due to the increase of available energy above maintenance when compared with the gestating sows. In Exp. 3, different feed drops used for delivering feed were evaluated. The Accu and the Ultra feed drops were more accurate than the Econo feed drop at angles of 90, 75, and 60°. The difference in accuracy is potentially related to the way that the drops attach to the feed line. However, the amount of feed that is collected in each drop appears to increase linearly as the feeder settings are increased. Thus, regression equations for the angle of the feed drop can be developed to adjust for the variability in the amount of accumulated feed. In Exp. 4, Alimet® was used to determine the TID TSAA:Lys ratio for ADG and G:F of 63 and 66% for Genetiporc and 61 and 56% for PIC pigs weighing between 10 to 20 kg. In Exp. 5, the optimal TID Lys:Calorie ratio was estimated to be 3.7 and 4.1 g Lys/Mcal ME for the Genetiporc and PIC pigs weighing between 10 to 20 kg . The ratios were than validated at two energy levels and the amount of TID Lys that was used for lean gain was similar for both genetic lines at approximately 20 g of Lys for each kg of gain.
Keywords: Feeding frequency; gestation; feed intake; feed drops; Agriculture, Animal Culture and Nutrition (0475)